2021
DOI: 10.1007/s11126-021-09907-w
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Psychiatric Consultations at Mental Health Center during COVID-19 Pandemic: Retrospective Observational Study

Abstract: The coronavirus pandemic and related social distancing measures have brought about dramatic changes in people's lives. In particular, health workers have been forced to change their activities both for the different needs of patients and for preventive measures against the spread of the virus. This study is aimed at comparing the urgent psychiatric consultations (UPC) performed at the outpatient Mental Health Center (MHC) of Modena during the coronavirus outbreak period, from 1 March to 31 August 2020, with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
(55 reference statements)
4
16
0
Order By: Relevance
“…Some of these, in fact, could only be carried out through telephone contact, such as consultancy with one’s nurse of reference, whereas other activities were totally suspended until the end of the state of emergency, such as group activities and semi-residential activities. 34 , 46 In accordance with some recent studies, despite remote interviews and telephone calls, the patient population taken into care by the outpatient services has received less psychological support and psychiatric treatments. 49 Concerns about tele-psychiatry have been expressed by both users and especially by professionals, reporting the loss of personal contact, which can limit the building of therapeutic relationship, although it can represent the only instrument now available to maintain the continuity of care in a regular setting.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Some of these, in fact, could only be carried out through telephone contact, such as consultancy with one’s nurse of reference, whereas other activities were totally suspended until the end of the state of emergency, such as group activities and semi-residential activities. 34 , 46 In accordance with some recent studies, despite remote interviews and telephone calls, the patient population taken into care by the outpatient services has received less psychological support and psychiatric treatments. 49 Concerns about tele-psychiatry have been expressed by both users and especially by professionals, reporting the loss of personal contact, which can limit the building of therapeutic relationship, although it can represent the only instrument now available to maintain the continuity of care in a regular setting.…”
Section: Discussionsupporting
confidence: 56%
“… 42 On the other hand, in 2020, we reported the increase of UPCs required by the most vulnerable people due to their clinical and/or social conditions, as suggested by the higher number of people living in psychiatric facilities and already treated in MHC, in line with the results of our previous study implemented in the outpatient Mental Health Center of Modena in the same period. 46 Although apparently in contrast with the general trend of UPCs, these results highlight the greater fragility of patients suffering from psychiatric pathology during pandemic, for whom ER remained the only place where they could ask for help, as suggested by other studies. 12 , 23 , 44 Patients staying at the facilities may have suffered from problems related to “forced coexistence”, 24 hours a day, with other residents due to the inevitably severe lockdown, applied in Italy especially from March to May 2020 to prevent the spread of the virus.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In particular, a French study reported an approximately 50% decrease in consultations performed for psychiatric emergencies in three different psychiatric centers in Paris, with an increase of consultations for only psychotic disorders in the pandemic period compared to 2019 ( 36 ). The reduction in the number of psychiatric consultations in outpatient services during the first period of 2020 compared with the same period in 2019 was also confirmed by Italian studies ( 37 , 38 ). A German study reports the reduction of psychiatric emergency consultations during March 2020 compared with March 2019, particularly for chronic affective psychiatric disorders ( 32 ).…”
Section: Introductionsupporting
confidence: 54%
“…However, recent studies of psychiatric emergency contacts show that regular out-patient contacts have decreased in all psychiatric patients since the pandemic, as a result of restricted face-to-face regulations, hinting at an non-selective decrease of admission rate for all psychiatric patients. [44][45][46] Finally, our results cannot be generalised to all other mental healthcare settings because of inherent differences in mental health service provision across the globe.…”
Section: Limitationsmentioning
confidence: 99%